Pharmacogenetic and Clinical Predictors of Clopidogrel Insufficiency in a Patient with Atherosclerosis Obliterans of the Lower Extremities: Clinical Case - M. A. Andreyanova; K. B. Mirzaev; D. A. Sychev; K. A. Ryzhikova; A. V. Pokrovsky; A. F. Kharazov (Столичная издательская компания, 2018)
The considered clinical case of combination of multifocal atherosclerotic vascular lesion with type 2 diabetes mellitus and liver fibrosis demonstrates a combination of polyvalent risk factors  for resistance to antiplatelet therapy with clopidogrel. The decrease in the effectiveness of prolonged therapy with P2Y12  inhibitor was clinically manifested by repeated thrombotic events and was confirmed by laboratorial VerifyNow P2Y12  Assay test system as a low percentage of inhibition of ADP-induced platelet aggregation. We established probable genetic predictors of the decrease in the effectiveness of antiplatelet therapy in this patient, namely, the  carriage of polymorphic markers  of the  ABCB1 CT, CES1 CA and  CYP3A4*22 CT genes  that determine the decrease in absorption, excessive hydrolysis of the drug and reduced activity of isoenzymes and transporters, that leads to disorders of active clopidogrel metabolite formation. A potential contribution of hepatic dysfunction to reduction in antiaggregant effect of P2Y12 inhibitor was demonstrated. Variant of drug interaction of clopidogrel and an inhibitor/substrate of P450 CYP2C19 - omeprazole, accompanied by a decrease in the effectiveness of antiplatelet therapy, was also considered.